Unveiling the Ecological Applications of Ancient DNA From Mollusk Shells - Der Sarkissian, Clio; Möller, Per; Hofman, Courtney A.; Ilsøe, Peter; Rick, Torben C.; Schiøtte, Tom; Sørensen, Martin Vinther; Dalén, Love; Orlando, Ludovic (Frontiers in Ecology and Evolution, 2020)
The shells of marine mollusks represent promising metagenomic archives of the past, adding to bones, teeth, hairs, and environmental samples most commonly examined in ancient DNA research. Seminal work has established that DNA recovery from marine mollusks depends on their shell microstructure, preservation and disease state, and that authentic ancient DNA could be retrieved from specimens as old as 7,000 years. Here, we significantly push the temporal limit for shell DNA recovery to ≥100,000 years with the successful genetic characterization of one Portlandia arctica and one Mytilus mussel sample collected within a dated permafrost layer from the Taimyr Peninsula, Russia. We expand the analysis of ancient DNA in carbonate shells to a larger number of genera (Arctica, Cernuella, Crassostrea, Dreissena, Haliotis, Lymnaea, Margaritifera, Pecten, Ruditapes, Venerupis) from marine, freshwater and terrestrial environments. We demonstrate that DNA from ancient shells can provide sufficient resolution for taxonomic, phylogenetic and/or population assignment. Our results confirm mollusk shells as long-term DNA reservoirs, opening new avenues for the investigation of environmental changes, commercial species management, biological invasion, and extinction. This is especially timely in light of modern threats to biodiversity and ecosystems.